Kunci membangun integritas bangsa Indonesia: Kunci membangun integritas bangsa Indonesia - Khoiriyah, Alya Miftakhul (Maliki Interdisciplinary Journal, 2026)
Corruption remains a serious challenge for Indonesia because it causes economic losses, hampers development, widens social inequality, and reduces public trust in government institutions. This study aims to analyze the importance of an anti-corruption culture as the key to building national integrity in Indonesia. The method used is a literature review by examining various sources related to anti-corruption culture, character education, national integrity, and good governance. The findings indicate that combating corruption cannot rely solely on law enforcement, but also requires a cultural approach that instills honesty, responsibility, discipline, justice, and social awareness. Character education plays a strategic role in shaping a generation with integrity from an early age through learning processes and exemplary conduct. In addition, the implementation of good governance principles such as transparency, accountability, and public participation can strengthen a clean governmental system. Synergy among government, society, families, and educational institutions is the main factor in fostering a sustainable anti-corruption culture. Therefore, an anti-corruption culture is an essential foundation for realizing a just, clean, dignified, and prosperous Indonesia for all citizens nationwide.